Improving justice responses for victims of intimate partner violence: examining the merits of the provision of independent legal representation - Walklate, Sandra (International journal of comparative and applied criminal justice, 2021)
Justice processes have long been criticised for their inability to meet the needs of intimate partner violence victims and provide remedies that facilitate recovery. Despite a bevy of victim-oriented reforms, victims continue to report dissatisfaction in their engagement with the legal process. Recognising the failures of policy responses to date, the Royal Commission into Family Violence (2016) in Victoria, Australia, sought to reimagine justice responses to victims of intimate partner violence through innovative models of reform, such as the introduction of legal representation for victims in court. In the absence of prescribed detail as to how this could be achieved, this article contends that there is a need to tread cautiously in this space. It sets out the potential benefits from trialling legal representation for victims in emerging Victorian specialist family violence courts, as well as the perceived risks that should be kept in mind prior to instituting state wide reform.